Influenza vaccination in elderly in Brazil in the period from 2016 to 2020 (Research, Society and Development, 2021)
This research aimed to evaluate the geographic distribution of applied portions of the influenza vaccine in the citizens aged 60 years or more, in the period from 2016 to 2020. The method was based on a cross-sectional study with consultation of the SUS database - DATASUS, evidencing a total of almost 7 million applied doses of the influenza vaccine during the study period, 1.4 million were for the elderly population, corresponding to 20% of the total vaccinated in that period. The year in which the large number of vaccine applications in the elderly population was recorded was 2016 and the smallest number was in 2018, with an enlarged in the backing years. Regarding geographic distribution, there was a greater number of vaccinated in the Southeast region. The region with the lowest number of doses applied was the Midwest region. It is concluded that, despite the observed decline in the quantity of doses applied over the period studied, there is still a greater concentration of doses requested in the Southeast region. Therefore, the dissemination of more health and information services is necessary to facilitate the access of the elderly population to vaccination.